Indywidualne doświadczenie pracy w warunkach ogniska wirusa SARS-CoV-2 – badania partycypacyjne w Domu Pomocy Społecznej w Choroszczy - Więcławski, Piotr (Kultura-Społeczeństwo-Edukacja, 2022)
The article is a presentation of the results of the research carried out in the Social Welfare Home in Choroszcz during the SARS-CoV-2 focal period in the facility. The analyzed research material was collected using the method of open participant observation of the social worker in the Social Welfare Home, carried out during the covid duty at the turn of September and October 2020. The purpose of the research was to show individual experiences of working in the conditions of a coronavirus outbreak and to identify the challenges resulting from increased social isolation. The article emphasizes the epidemiological situation in the facility related to: staff shortages, psychophysical condition of employees and residents, limitations in working with mentally suffering people, the needs of residents experiencing increased social isolation, difficulties in implementing the assumptions of social rehabilitation and occupational therapy. There was also an assessment of good operating rehabilitation practices in the covid sub-unit using modern technologies.